Immunophenotypic analysis of hematopoiesis in patients suffering from Shwachman–Bodian–Diamond Syndrome. (10th February 2015) - Mercuri, Angela; Cannata, Elisa; Perbellini, Omar; Cugno, Chiara; Balter, Rita; Zaccaron, Ada; Tridello, Gloria; Pizzolo, Giovanni; De Bortoli, Massimiliano; Krampera, Mauro; Cipolli, Marco; Cesaro, Simone
Abstract Objectives Shwachman–Diamond syndrome is a rare disorder characterized by exocrine pancreatic insufficiency, skeletal abnormalities, and bone marrow failure, with high risk of leukemic evolution. The aim of the study was the immunophenotypic characterization of bone marrow cells from patients with Shwachman–Diamond syndrome to assess the maturation pathway of blood progenitor cells and to identify the presence of recurrent abnormalities. Methods Bone marrow samples from nineteen patients and eleven controls were analyzed by multiparameter flow cytometry. Results We found a low frequency of CD34+ cells (P = 0.0179) and myeloid progenitors (P = 0.025), in the bone marrow of patients with Shwachman–Diamond syndrome as compared to the controls. A significant reduction in the percentage of granulocytes (P = 0.002) and an increase of monocytes (P < 0.001) were also evident in the bone marrow of patients. Conclusions On the basis of these observations, future prospective assessments may be useful to verify the contribution of bone marrow immunophenotype in the early identification of the evolution toward aplasia or myelodysplasia.